Emotional intelligence in the educational field: a meta-analysis - Puertas Molero, Pilar; Zurita-Ortega, Félix; Chacon-Cuberos, Ramon; Castro-Sanchez, Manuel; Ramirez-Granizo, Irwin; Gonzalez Valero, Gabriel (Anales de Psicología / Annals of Psychology, 2020)
Currently Emotional Intelligence is a key factor that affects the social and mental wellbeing of students, helping them to regulate and manage their emotions, which makes it easier for them to understand their environment and make the right decisions in the face of the different stressful moments that arise daily in class. which emphasizes that it must be a continuous and progressive element developed through educational entities. Hence the intention to carry out a meta-analysis in order to know the degree of reliability as well as the benefits reported by the programs of implementation of Emotional Intelligence in the students. The bibliographic search was carried out in the Web of Science, SCOPUS and PubMed database, obtaining a total of 20 articles published in the last two decades related to the subject analyzed and which met the inclusion criteria. Only longitudinal articles were included with which a meta-analysis was carried out, obtaining an average effect size of 0.73, analyzing in turn the effectiveness according to educational stage and duration of implementation, with Primary Education obtaining the best results. results according to the application of the programs (TE = 0.95), followed by Secondary Education, in turn, the effectiveness of the interventions was analyzed according to the duration of the program, obtained that the medium-term programs were the ones that reported the best results to the students. Reaching the conclusion that most of the programs contribute to the development and empowerment of the Emotional Intelligence of the students, equipping them with the necessary skills to face the situations that take place on a daily basis, as well as the ability to feel self-realized with the tasks carried out and with the applied effort.